2019
DOI: 10.1111/ejss.12912
|View full text |Cite
|
Sign up to set email alerts
|

The effects of straw incorporation with plastic film mulch on soil properties and bacterial community structure on the loess plateau

Abstract: The application of plastic film mulch and the return and incorporation of crop straw into topsoil as independent treatments affect soil physicochemical properties, including nutrient balance/cycling. It remains unclear whether combining straw incorporation and plastic film mulch significantly affects soil physicochemical properties and bacterial communities. We conducted a two‐factor (plastic film mulch application and maize straw incorporation) randomized block design experiment with four treatments: no plast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 91 publications
(113 reference statements)
2
24
0
Order By: Relevance
“…Soil mulching is a widely used method in crop cultivation and offers many advantages [13]. For example, mulching improves soil moisture retention, facilitates early crop growth and development, changes soil physical and chemical properties, and reduces weeds, all of which contribute to higher crop yields [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil mulching is a widely used method in crop cultivation and offers many advantages [13]. For example, mulching improves soil moisture retention, facilitates early crop growth and development, changes soil physical and chemical properties, and reduces weeds, all of which contribute to higher crop yields [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Plastic film mulch is a common soil mulch, which is widely used in arid and semiarid areas of China and has become an important technology in agricultural production [2,16,17]. Mulching can significantly improve soil structure, increase soil water retention capacity, and promote crop growth and yield [2,13,15]. Zhou et al [19] showed that plastic film mulching significantly increased both the aboveground and belowground biomass of maize.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular ecological network analysis (MENA) 6 was used to demonstrate the relationship between the rhizosphere bacterial communities of the two sugarcane cultivars and environmental factors ( Li Y. et al, 2019 ). Networks were constructed for the root-associated area and the soil communities based on the relative abundances of OTUs, resulting in two networks.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have revealed that changes in the soil environment can significantly affect soil bacterial communities (Kaiser et al ., 2016;Li et al ., 2019;Huang et al ., 2019;Wang et al ., 2019). The RDA analysis showed that changes in the soil bacterial community structure were driven by SOC, C: N ratio, TN, pH, and MWD ( Figure 6), as reported elsewhere (Li et al ., 2019;Kaiseret al ., 2016).…”
Section: Controlled-release Fertilizer and Plastic-film Mulching Chanmentioning
confidence: 99%
“…Studies have revealed that changes in the soil environment can significantly affect soil bacterial communities (Kaiser et al ., 2016;Li et al ., 2019;Huang et al ., 2019;Wang et al ., 2019). The RDA analysis showed that changes in the soil bacterial community structure were driven by SOC, C: N ratio, TN, pH, and MWD ( Figure 6), as reported elsewhere (Li et al ., 2019;Kaiseret al ., 2016). Soil microorganisms drive the metabolism of carbon in the soil (Fierer et al ., 2009, Wallenstein, 2012, and SOC is a key property affecting the soil bacterial community structure (Liet al ., 2019).…”
Section: Controlled-release Fertilizer and Plastic-film Mulching Chanmentioning
confidence: 99%